The composition, diversity, and distribution of mosquito fauna (Diptera: Culicidae) in Kosovo. Issue 1 (23rd May 2019) - Muja‐Bajraktari, Nesade; Zhushi‐Etemi, Ferdije; Dikolli‐Velo, Enkelejda; Kadriaj, Perparim; Gunay, Filiz
ABSTRACT: The aim of this study is to identify the mosquito species that currently exist and their distributions in Kosovo in order to determine current potential endemic zones and areas at a higher risk for future epidemics. These scientific data will be shared with public health authorities for implementing mosquito control programs. During a two‐year period of monitoring in 48 localities in 23 provinces in Kosovo, a total of 1, 604 mosquitoes representing 13 species and six genera were collected and morphologically identified. Members of species complexes were also classified to species using DNA barcoding. In total, 13 species were identified with Culex pipiens s.l ., the predominant species with an abundance rate of 39%. The remaining 12 species identified were grouped into five genera: Anopheles, Aedes, Coquillettidia, Culiseta, Uranotaenia, including species that are vectors of arboviruses in other parts of the world.